Outcomes of diverting loop ileostomy reversal in the elderly: a case–control study. Issue 6 (18th April 2021) - Segev, Lior; Assaf, Dan; Elbaz, Nadav; Schtrechman, Gal; Westrich, Gal; Adileh, Mohammad; Nissan, Aviram; Goitein, David
Abstract: Background: Although diverting loop ileostomy (DLI) reversal is considered to be a relatively simple procedure, it is not immune from major morbidity. We aimed to compare outcomes of DLI reversal between elderly and non‐elderly patients. Methods: Retrospective review of all patients who underwent DLI reversal at a single tertiary medical centre between 2010 and 2020. The elderly group consisted of patients 70 or older compared to a control group of those younger than 70 years. Results: During the study period, 307 patients underwent DLI reversal. Of these, 76 patients were in the elderly group (mean age 75.6) and 231 in the control group (mean age 55.3). The groups were comparable in terms of mean time interval between the creation of the ileostomy and reversal (242 versus 255 days, respectively, P = 0.5), choice between stapled and hand‐sewn anastomoses (97.4% stapled anastomosis versus 93.1%, P = 0.086), median post‐operative length of stay (5 days in both, P = 0.086), rates of post‐operative complications (26.3% versus 26.8%, P = 0.99), severe complications (5.3% versus 6.9%, P = 0.81) and 30‐day readmission rates (13.2% versus 10.8%, P = 0.58). Multivariate analysis found the time interval between the creation of the stoma and its reversal to be the only significant risk factor for major post‐operative morbidity. Age was not found to be correlated with post‐operative morbidity. Conclusion: The outcomes of loop ileostomy reversal in elderly patients are similar to non‐elderly patients. Efforts should be made to decrease the time interval between the creation of the stoma and its reversal as this is a significant risk factor for major post‐operative morbidity. Abstract : Advanced age is not a risk factor for increased morbidity after diverting loop ileostomy (DLI) closure. Though relatively a simple and short procedure, DLI closure is associated with substantial overall complications rates and non‐negligible severe complications rate. This should be taken into account when deciding to construct the ileostomy and prior to its closure. Efforts should be made to minimize the time interval between DLI creation and reversal of the ileostomy.